Brachymeria mochica, a new Neotropical species of Chalcididae (Hymenoptera: Chalcidoidea) discovered on the archaeological site of Huacas de Moche, Peru with a review of related species - Delvare, Gérard; Huchet, Jean-Bernard (Zootaxa, 2017)
Two parasitoid wasp species of the Brachymeria minuta species group are studied. The specimens were collected in Peru at the archaeological site of Huacas de Moche, the former capital of the Mochica culture between 400–600 A.D. Brachymeria mochica Delvare sp. nov. (Chalcididae) is described and illustrated while B. podagrica (Fabricius, 1787) is reviewed with an update of the nomenclature and a summary of knowledge regarding its hosts and biology. The morphology and biology of both species are newly defined and characterized. Brachymeria brevicornis (Klug, 1834) stat. rev., previously synonymized with B. minuta (Linnaeus, 1767), is re-established as a valid species and a lectotype is designated. The following names are synonymised with B. podagrica: Chalcis ferox Kieffer, 1905 and its variety C. ferox coxalis Kieffer, 1905, Chalcis spilopus Cameron, 1905, Chalcis capensis Cameron, 1905, Chalcis transvaalensis Cameron, 1911, Chalcis neglecta Masi, 1916, Chalcis sodalis Masi, 1917, Brachymeria Fonscolombei var. gananensis Masi, 1938, Chalcis vulcani Schmitz, 1946, and Brachymeria fonscolombei f. neglecta Masi, 1951 new synonymies. Brachymeria amenocles (Walker, 1846) stat. rev. is re-established as a valid species with Chalcis varipes Walker, 1871 and Brachymeria Beccarii Masi, 1929 as junior synonyms syn. rev. Lectotypes are designated for the above names except for C. sodalis and C. vulcani.